2013
DOI: 10.1093/mnras/stt1824
|View full text |Cite
|
Sign up to set email alerts
|

New Compton-thick AGN in the circumnuclear H2O maser hosts UGC 3789 and NGC 6264

Abstract: Large column densities, derived from X-ray studies, are typically measured towards AGN hosting water masers, especially when the H 2 O emission is associated with the nuclear accretion disk. In addition, possible correlations between the intrinsic X-ray luminosity and the characteristics of the H 2 O maser emission have been put forward that, however, require confirmation. We have performed high-sensitivity XMM-Newton observations of a sample of five H 2 O maser sources confidently detected in our ongoing surv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 73 publications
9
48
1
Order By: Relevance
“…UGC 3789 has a black hole mass of (1.4±0.05)× 10 7 M ( Kuo et al 2011). In addition, Castangia et al (2013) classified UGC 3789 as a Compton-thick galaxy (N H > 10 24 cm −2 ). Radio emission is observed at the center of our 33 GHz map.…”
Section: J2000mentioning
confidence: 99%
“…UGC 3789 has a black hole mass of (1.4±0.05)× 10 7 M ( Kuo et al 2011). In addition, Castangia et al (2013) classified UGC 3789 as a Compton-thick galaxy (N H > 10 24 cm −2 ). Radio emission is observed at the center of our 33 GHz map.…”
Section: J2000mentioning
confidence: 99%
“…The nearby barred galaxy NGC 613 (figure 1) hosts a lowluminosity AGN, which is identified through mid infrared spectroscopy (Goulding & Alexander 2009) and X-ray observations by using the XMM-Newton (Castangia et al 2013). NGC 613 is one of the best targets for studying the jet/outflow activities due to the proximity (17.5 Mpc; Tully 1988), relatively abundant Schöier et al 2005) molecular gas around the center (e.g., Elfhag et al 1996), activity shown by the radio jet (Hummel et al 1987), and nuclear ring with moderate inclination (i ∼ 55 • , Hummel & Jorsater 1992).…”
Section: Introductionmentioning
confidence: 99%
“…So far, over 4000 galaxies have been searched for 22 GHz water emission with only 150 detections and nearly 500 galaxies have been surveyed for hydroxyl emission with 120 detections (see Wagner 2013 and references therein). Many attempts to link megamasing of either molecular species to other galaxy observables have largely been met with only modest success (e.g., Darling & Giovanelli 2006;Zhu et al 2011;Zhang et al 2012), but significant connections have been achieved, linking OH megamasers to large dense gas fractions (Darling 2007) and water emission to high column densities (Zhang et al 2006;Castangia et al 2013), large X-ray luminosities (Kondrakto et al 2006), and high corrected [O III]/ Hβ (Constantin 2012). Luminous OH emission is frequently powered by starbursting in LIRG/ULIRG galaxies while water megamasers are usually associated with AGNs (Lo 2005;Pihlström 2007).…”
Section: Introductionmentioning
confidence: 99%